2019
DOI: 10.3233/bmr-181172
|View full text |Cite
|
Sign up to set email alerts
|

Learning effect of dynamic postural stability evaluation system

Abstract: The study showed that balance test scores stabilized at different sessions from 1st to 3rd assessment period. Maximum normalized scores were reached at the third trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Despite the fact they did not differ significantly, a clear tendency was observed for higher results in the control session, in the case of easier tasks (EO and EC). Potentially, this could be connected with the learning effect but previous studies demonstrated that this can occur only in more demanding tasks like during a narrow stance with eyes closed 49 or standing on foam 50 among young healthy subjects. Moreover, to reduce the possibility of this phenomenon, familiarization, randomization of trials order, and averaging results of two trials for each test version were applied in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact they did not differ significantly, a clear tendency was observed for higher results in the control session, in the case of easier tasks (EO and EC). Potentially, this could be connected with the learning effect but previous studies demonstrated that this can occur only in more demanding tasks like during a narrow stance with eyes closed 49 or standing on foam 50 among young healthy subjects. Moreover, to reduce the possibility of this phenomenon, familiarization, randomization of trials order, and averaging results of two trials for each test version were applied in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…The usefulness of hand grip strength measurements to document intervention changes has recently received scrutiny, and a lack of intervention effects in this parameter are therefore not unsurprising especially in a highly active and healthy population [30]. Although Lichtenstein et standardized practice trials were performed, high learning effects are likely to occur in balance testing and a high baseline-level might have caused a ceiling effect of results [31,32]. Englund and colleagues [17] found improvements in maximum walking speed of 11.4%, while in this study the agility training group maintained their performance compared to the control group that got 2.9% slower but improvements in the multi-task conditions were in the range of 5 to 6%.…”
Section: Discussionmentioning
confidence: 99%
“…The recorded parameters will be the same as those for standing postural control. Prior, participants will practise by performing two unrecorded tests in each direction to avoid learning bias 37. If the test is stopped in case of balance loss, the participants may retry the test a maximum of five times.…”
Section: Methods and Analysismentioning
confidence: 99%